If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (P + -3)(3p + 1) = 0 Reorder the terms: (-3 + P)(3p + 1) = 0 Reorder the terms: (-3 + P)(1 + 3p) = 0 Multiply (-3 + P) * (1 + 3p) (-3(1 + 3p) + P(1 + 3p)) = 0 ((1 * -3 + 3p * -3) + P(1 + 3p)) = 0 ((-3 + -9p) + P(1 + 3p)) = 0 (-3 + -9p + (1 * P + 3p * P)) = 0 (-3 + -9p + (1P + 3pP)) = 0 Reorder the terms: (-3 + 1P + -9p + 3pP) = 0 (-3 + 1P + -9p + 3pP) = 0 Solving -3 + 1P + -9p + 3pP = 0 Solving for variable 'P'. Move all terms containing P to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 1P + -9p + 3 + 3pP = 0 + 3 Reorder the terms: -3 + 3 + 1P + -9p + 3pP = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 1P + -9p + 3pP = 0 + 3 1P + -9p + 3pP = 0 + 3 Combine like terms: 0 + 3 = 3 1P + -9p + 3pP = 3 Add '9p' to each side of the equation. 1P + -9p + 9p + 3pP = 3 + 9p Combine like terms: -9p + 9p = 0 1P + 0 + 3pP = 3 + 9p 1P + 3pP = 3 + 9p Reorder the terms: -3 + 1P + -9p + 3pP = 3 + 9p + -3 + -9p Reorder the terms: -3 + 1P + -9p + 3pP = 3 + -3 + 9p + -9p Combine like terms: 3 + -3 = 0 -3 + 1P + -9p + 3pP = 0 + 9p + -9p -3 + 1P + -9p + 3pP = 9p + -9p Combine like terms: 9p + -9p = 0 -3 + 1P + -9p + 3pP = 0 The solution to this equation could not be determined.
| 108+256x^3=0 | | 4x+9-3x-4= | | 81+18b+b^2= | | 0.4=x | | (4+7)(5y+7)=0 | | 6(3+8x)=-318 | | -2(5x-6)-(3x+3)= | | 8(.06m+21.80+.20(21.80))=241.92 | | -13c-35=9-2e | | 8x+7=6x+35 | | 2(4g-3)-8=4+2x | | 3x+27=195 | | -6(3w+5)+3w+5=w-45 | | 1(21)-2=19 | | n-(-12)=23 | | 10x+9-11-X=-4x-8-6x-6 | | 7p^2=17p-6 | | 65x+74=2089 | | (6x-1)-(10x-15)=0 | | 15=1+16t-4t^2 | | x+2x-3=5 | | 8(z+2)-4(3z+1)= | | 9(2n-2)=(4n+2)+1 | | 3x+6=393 | | 36.71=11.11+3.4t | | 27x^2+9y^2=0 | | 20x=10y+8 | | 2y-86=22x | | -2y-7-4y+8= | | 8x^2+8x=22 | | .5(2x-6)=6 | | 3b-5=8(6+5b) |